Learnings from the evaluation of HERrespect: a factory-based intervention to prevent intimate partner and workplace violence against female garment workers in Bangladesh - Ruchira Tabassum Naved; Mahfuz Al Mamun; Kausar Parvin; Samantha Willan; Andrew Gibbs; Rachel Jewkes (Taylor & Francis Group, 2021)
Background: Intimate partner violence (IPV) and workplace violence (WPV) against women are widespread globally, and we set out to establish whether an intervention on gender-transformative programming delivered to Bangladeshi garment factory workers could reduce women's experience of IPV and WPV. We developed and tested an intervention, HERrespect and encountered considerable obstacles. Objective: To describe the challenges in program implementation and evaluation in the factories and the serious implications that arose for the study outcomes. Methods: HERrespect is a participatory intervention with mostly parallel group sessions for female and male workers and the management staff, designed to be delivered weekly in three hourly sessions, and supported by some factory-wide and limited community information campaigns. It was evaluated in a quasi-experimental study conducted in eight garment factories in and around Dhaka city, with a cohort of 800 women workers and 395 management staff who were followed for 24 months. Results: The study was conducted in the ready-made garment industry with substantial power imbalances between buyers, factory management and workers. The factories were contacted through the buyers, and some factories had agreed to participate half-heartedly. Many did not make enough time available for optimal implementation. Thus, the sessions were shortened and spread out. The factories did not make all the group members available for sessions. Whilst agreeing to participate, some management undermined the research by warning workers against disclosing information that may harm the business, resulting in the endline data being unreliable. Conclusions: Future research on IPV prevention in this sector is advised to: (1) Gain genuine management buy-in prior to starting activities; (2) implement an optimally intensive programme for the workers and management; (3) engage men from the female workers' communities. WPV prevention will require a change in the structural violence of the just-in-time regime which contributes largely to WPV.